2018
DOI: 10.1371/journal.pone.0209076
|View full text |Cite
|
Sign up to set email alerts
|

Level and determinants of birth preparedness and complication readiness among pregnant women: A cross sectional study in a rural area in Bangladesh

Abstract: BackgroundIncreasing the level of birth preparedness and complication readiness (BP/CR) is one of the key interventions to promote optimal utilization of skilled maternal health services. It is therefore essential to determine the women’s ability to recognize the danger signs and the level of BP/CR. This information can be used to design more effective health interventions.ObjectivesThis study was conducted to determine the knowledge in recognition of maternal complications, and the level and factors associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
24
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 34 publications
12
24
2
1
Order By: Relevance
“…Poor understanding of complications, combined with the lack of contextual health education, might lead to less timely attendance at ANC. Similar to our ndings, another study in Matlab, Bangladesh, reported that only 26% of women had good knowledge of pregnancy complications [15]. Several studies have showed that ANC utilization is associated with women's knowledge about pregnancy complications [15,60,61].…”
Section: Name Of Health Facilitysupporting
confidence: 89%
See 3 more Smart Citations
“…Poor understanding of complications, combined with the lack of contextual health education, might lead to less timely attendance at ANC. Similar to our ndings, another study in Matlab, Bangladesh, reported that only 26% of women had good knowledge of pregnancy complications [15]. Several studies have showed that ANC utilization is associated with women's knowledge about pregnancy complications [15,60,61].…”
Section: Name Of Health Facilitysupporting
confidence: 89%
“…Similar to our ndings, another study in Matlab, Bangladesh, reported that only 26% of women had good knowledge of pregnancy complications [15]. Several studies have showed that ANC utilization is associated with women's knowledge about pregnancy complications [15,60,61]. Women with poor knowledge of pregnancy complications are likely to also be unfamiliar with the consequences of the conditions.…”
Section: Name Of Health Facilitysupporting
confidence: 86%
See 2 more Smart Citations
“…Levels of BP/CR vary across the literature and are generally low [9]. Socio-demographic characteristics, including age, parity and education as well as socio-economic factors, such as income, have been shown to influence BP/CR across different socio-cultural settings.…”
Section: Introductionmentioning
confidence: 99%